Needs Assessment of Emergency Department Residents in Examining and Managing Patients with Ophthalmologic Complaints - Wang, Kaidi; Williams, Sarah R.; Chong, Ian; Fredrick, Douglas R. (Journal of Academic Ophthalmology, 2019)
Purpose Emergency medicine residents are trained to deal with a variety of emergency conditions; eye emergencies represent only a small portion of their clinical experience. This study was a targeted needs assessment of the comfort level of emergency medicine residents in diagnosing and managing patients who present with an ophthalmic chief complaint, with the goal of targeting future educational interventions.Methods This was a cross sectional survey conducted at a large tertiary-care hospital between June 2016 and August 2016. Participants were 1st, 2nd, or 3rd year emergency medicine residents in an Accreditation Council for Graduate Medical Education (ACGME)-approved emergency medicine residency.Results The total response rate was 67.4% (29/43). The majority of residents did not expect equivalent availability of ophthalmology consultation services post-graduation. They generally believed ophthalmology and examination skills to be important to their future career and became more comfortable with the slit lamp exam through residency, although the average level of comfort was only 6.9 on a 1 to 10 scale for 3rd year residents (standard deviation [SD] = 2.6). A majority of residents were not confident with their diagnostic, examination, or management skills when queried about specific ophthalmic conditions or presenting symptoms. They indicated a variety of reasons why their comfort with ophthalmologic patients was limited.Conclusion There is both need and desire for increased ophthalmic skills training for emergency medicine residents. Given time constraints in residency training, possible solutions will need to be innovative and multifaceted in order to target this goal.
Keywords: emergency medicine; educational interventions; ophthalmology